Labor and Economic Growth in Zimbabwe - Chidoko, Clainos (The Economics and Finance Letters, 2014)
The study investigates the impact of labour on economic growth in Zimbabwe. The research uses a simple Ordinary Least Squares regression modeling method. The results suggest that labour and capital impact positively on Zimbabwe’s economic growth. The study recommends the government to pursue an employment-intensive strategy. It also recommends the government to develop an education and training system geared towards employment creation.